Faktor-Faktor yang Mempengaruhi Struktur Modal (Studi Empiris Perusahaan Industri Non Cyclicals 2017-2019) - Saputro, Ahmad Eko; Setiawan, Andik; Usuli, Sudarto (Jurnal Ilmiah Poli Bisnis, 2022)
This study aims to determine the effect of profitability, liquidity, and inflation on Non-Cyclical Consumer Sector Companies. The data used in this study are the 2017-2019 financial statements of 45 companies listed on the IDX and inflation data at BI. Capital Structure is proxied by Debt to Equity (DER), Profitability is proxied by Return On Assets (ROA), liquidity is proxied by Current Ratio (CR), and Inflation is measured by consumer price index (CPI), Company Size is proxied by Total Assets as a variable control . The results of this study are partially profitability has a negative effect (coefficient value -1.68) and significant alpha 5% (0.000 <0.05), Liquidity has a negative effect (coefficient value -9.22) and significant alpha 5% (0.000 < 0.05). Inflation has a positive effect (coefficient value 20.291) and a significant alpha 10% (0.094 <0.10). Profitability, liquidity, and inflation together affect the capital structure and have a contribution of 68.4% % (coefficient of determination R2 = 0.684).